Kebijakan Hukum Pidana Pembebasan Bersyarat Bagi Pelaku Tindak Pidana Pembunuhan - Mahendra Putera Septyano; Khairina Laksita Nur A; Nabilla Febiyanti; Nadia Ardyta Zahrani; Windy Arta Pitasari; Diva Pasanta Diani (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
This article discusses the legal policy of parole for criminals, especially serious crimes such as murder, in the context of the penal system in Indonesia. Conditional release is an opportunity given to mechanics to serve the remainder of their sentence outside the Correctional Institution (Lapas) under special supervision. The aim is to encourage rehabilitation so that they can reintegrate into society in a positive way. The juridical analysis in this research focuses on factors that influence the implementation of requirements, which include law, law enforcement officials, facilities and infrastructure, the role of society, and culture. This study uses a qualitative approach. The research results show that conditional forgiveness can function as a compensatory rehabilitation process if carried out with strict supervision and assessment.